2000
DOI: 10.1074/jbc.275.12.8448
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Domain of MutY Glycosylase Determines the 7,8-Dihydro-8-oxo-guanine Specificity and Is Crucial for Mutation Avoidance

Abstract: Escherichia coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 60 publications
8
87
0
Order By: Relevance
“…hMYH binding to 8oxoG/AP might prevent its action till the abasic site has been fully repaired. Consistent with this model, Li et al (2000) have shown that the tight binding of MUTY to 8oxoG/AP and also to 8oxoG/T and 8oxoG/G has an inhibitory effect on Fpg activity.…”
Section: Discussionsupporting
confidence: 66%
“…hMYH binding to 8oxoG/AP might prevent its action till the abasic site has been fully repaired. Consistent with this model, Li et al (2000) have shown that the tight binding of MUTY to 8oxoG/AP and also to 8oxoG/T and 8oxoG/G has an inhibitory effect on Fpg activity.…”
Section: Discussionsupporting
confidence: 66%
“…OGG1 is able to remove 8-oxoG from T/8-oxoG and G/8-oxoG efficiently in vitro (30,31,38). Our laboratory has data to indicate that MutY protein can block and regulate MutM activity (2). Similar to the E.coli MutY/MutM interaction, MYH binding to T/8-oxoG and G/8-oxoG may inhibit OGG1 activity with these substrates.…”
Section: Discussionmentioning
confidence: 73%
“…Over a short reaction period the rate of cleavage of calf mtMYH was much faster for the A/8-oxoG mismatch than other substrates. This substrate reactivity is similar to that of E.coli MutY (2,57,58). In view of the fact that mitochondrial OGG1-like protein will cleave 8-oxoG-containing mismatches and not mismatches paired with G, it is of biological importance that mtMYH binds tightly to A/8-oxoG mismatches but not A/G or A/C mismatches.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The N-terminal domain of E. coli MutY has the catalytic activity (36 -40); however, the C-terminal domain is important for GO recognition (36,37,40,41). The PCNA binding motifs located at the Cterminal ends of eukaryotic MYH are not conserved in bacterial MutY proteins.…”
Section: The Interactions Between Myh and Pcna Proteins From Both S mentioning
confidence: 99%